The impact of medical student research as a discussion topic during the residency interview process - Kelly Daus (BMC, 2021)
Abstract Background Students with a greater number of research experiences are more successful in the National Residency Match Program (NRMP.) As a result, approximately two-thirds of allopathic medical schools have implemented a scholarly research project (SP) as a part of their curriculum. While inclusion of an SP in the medical school curriculum increases research productivity, literature to date has not investigated the frequency with which it is a discussion topic during residency interviews. Methods One hundred twenty-three students from the graduating class of 2019 and 2020 at the University of Arizona College of Medicine - Phoenix (UACOMP) completed a 17-question survey examining the student’s SP and whether they completed additional research, with an overall response rate of 82.6%. Survey participants were asked to quantify how many residency interviewers asked about their SP or additional research during the interview process. Results Twenty-seven percent of interviewers asked students about their SP and 41% of interviewers asked students about additional non-SP research. 40% of interviewers asked about research overall to include SP and/or non-SP research. A greater percentage of interviewers (50%) asked students about their SP if they had undertaken additional research compared to interviewers of students who did not undertake additional research (29%, p = 0.0237). A greater percentage of interviewers at academic institutions (31%) asked students about their SP, compared with a smaller percentage of interviewers at predominantly non-academic programs (22%, p = 0.0054). There were no significant differences in the proportion of interviewers asking about the SP based on the type of specialty, competitiveness of specialty, relatedness project topic to specialty, and publication/presentation status of project. Conclusion Student research experiences may serve as a frequent discussion topic during the residency interview. Approximately one-quarter of interviewers ask about the SP regardless of specialty, research topic, and publication/presentation status of the project. Students with additional research experiences beyond their SP may experience a higher percentage of interviewers asking about their SP. Also, students applying to predominantly academic programs may experience a higher proportion of interview questions about research compared to peers interviewing at non-academic programs.